Padrões de comportamentos de risco para doenças crônicas não transmissíveis no Brasil - Duarte, Ana Paula Pereira (2017)
Introduction: Behaviors such as abusive alcohol consumption, smoking, sedentary behavior, insufficient physical activity and unhealthy eating habits are considered as modifiable risk factors for chronic noncommunicable diseases (NCD). These behaviors may not occur in isolation and their aggregation increases the risk of developing NCD. Objective: To identify patterns of risk behavior for chronic non-communicable diseases in the Brazilian population and to analyze associated sociodemographic and economic factors. Method: A cross-sectional study, with data from the National Health Survey, a household-based survey with national representation, conducted in 2013 in Brazil, with 60,202 individuals (≥18 years of age). In order to identify the patterns of risk behaviors, the principal components analysis was used, through factor analysis, considering the following behaviors: consumption of (a) processed soft drinks/juices, (b) sugary foods, (c) Consumption of meats with excess fat, (d) chicken with skin and (e) abusive consumption of alcoholic drinks; (f) smoking; (g) Leisure time physical inactivity; (h) sedentary behavior and (i) inadequate consumption of fruits and vegetables (FLV). Retention pattern scores were categorized into quartiles, and intermediate quartiles (2nd and 3rd quartiles) were combined to facilitate the interpretation of associations with demographic and socioeconomic characteristics. The study design and sample weights were considered in the statistical analyzes. Results: Four patterns, named "Saturated fat", "Alcohol and Smoke", "Sedentary behavior and Sugars" and "Physical inactivity and Low consumption of FLV" were identified, explaining 54.09% of the total variance. Greater adherence to the standards "Saturated fat" and "Alcohol and Smoke" was observed among men, with lower level of education and residents in the Central-West Region. The patterns "Sedentary behavior and Sugars" and " Physical inactivity and low consumption of FLV" showed differences among the regions and greater adhesion among the women; the first, was associated with young people (18-24 years old) and with higher schooling and the second, was associated with older age (≥ 60 years) and lower schooling. Conclusion: The consumption of saturated fat the main pattern identified. Men showed greater adherence to the standards "Saturated fat" and "Alcohol and Smoke", and the women to the standards "Sedentary behavior and Sugars" and "Physical inactivity and Low consumption of FLV". In general, there was greater adherence to the patterns of risk behaviors among the young/adults and in the population with low level of schooling. The identification of these patterns can contribute greatly to the planning of public strategies for the prevention of chronic noncommunicable diseases and health promotion.